Gross alpha and beta activities in drinking water from Goiás state, Brazil (Brazilian Journal of Radiation Sciences (BJRS), 2019)
Detection of gross alpha and beta radioactivity is important for a quick surveying of both natural and anthropogenic radioactivity in water. Furthermore, gross alpha and gross beta parameters are included in Brazilian legislation on quality of drinking water. In this work, a low background liquid scintillation spectrometer was used to simultaneously determine gross alpha and gross beta in samples of the public water supplies in the state of Goiás, Brazil, during 2010-2015. Sample preparation involved evaporation to concentrate the sample ten-fold. The results indicate that the water meets the radioactivity standards required by the regulations MS 2914/2011 of the Brazilian Department of Health. Concerning the high level of censored observations, a statistical treatment of data was conducted by using analysis methods of censored data to provide a reference value of the gross alpha and beta radioactivity in drinking water from the state of Goiás. The estimated typical activities are very low, 0.030 Bq.L-1 and 0.058 Bq.L-1, for gross alpha and gross beta, respectively.